The lives of ordinary people in ancient Israel: where archaeology and the Bible intersect - Dever, William G. (Eerdmans, 2012)
On history and history writing -- The challenges of writing a history of ancient Israel -- The natural setting -- The database: sites and hierarchies -- Cities and towns -- Towns, villages, and everyday life -- Socioeconomic structures -- Religion and cult -- Israel's neighbors -- Warfare and the end